Intimate partner violence directed at men: Experiences of violence, help-seeking, and potential gender role conflict among Portuguese men - Reis, E.; Moleiro, C.; Arriaga, P. (Sexuality and Culture, 2024)
Recent research has shed light on how men in same-sex and different-sex relationships experience Intimate Partner Violence (IPV), and how it may contribute to their Gender Role Conflict (GRC), through which men face a dissonance with their gender roles. However, knowledge on these topics is still lacking. We aim to better understand men’s experiences of violence in their same-sex or different-sex relationships by identifying their dynamics and the specific barriers and facilitators to seeking help. Semi-structured interviews were conducted with 14 adult men (Heterosexual, n = 6; Gay, n = 5; Bisexual, n = 2; Not disclosed, n = 1) who self-identified as having been targets of IPV. The interview protocol considered the literature on IPV and the feedback from stakeholders in victim support services. The results were analyzed following the principles of Content Analysis. Our findings suggest that men are negatively impacted by their abusive relationships, with physical, psychological, sexual, and economic violence having been perpetrated by their same-sex or different-sex partners. Some men reported being further stigmatized in their help-seeking experiences. Gay and bisexual men indicated specific processes that played a significant role in their experiences. Some men revealed discomfort with the identity of “victim”, which may be linked to possible GRC processes. In sum, IPV impacts men in different-sex and same-sex relationships, and our findings provide new insights about how violence and help-seeking are experienced in the Portuguese cultural setting. Future efforts should focus on assessing possible GRC processes in this population and provide adequate information and tailored services to the specific needs of these men.